Market Survey On Consumption Pattern Of Street Food Products In Prayagraj District (Journal of Pharmaceutical Negative Results, 2023)
There is a dearth of knowledge regarding the consumption habits of street foods, despite the fact that individuals in low- and middle-income nations rely heavily on SF for their diet. An online survey employing a structured questionnaire was used to perform a cross-sectional study on 200 street food consumers in the Prayagraj/Allahabad District. Customers were approached and requested to participate who went to the randomly sampled Street Foods vendors and stores. The majority of consumers were male, between the ages of, and had at least a 10+2 and a Bachelor's degree. The primary findings showed that 91.5% of these consumers virtually always ate street food. In Prayagraj/Allahabad District, the most frequently consumed items were various types of street food products. chaat, bun, samosa, kachauri/khasta, fritters, south and north Indian chow mein, non-vegetarian, eggs, and dried goods. Consumers answered that they would prefer to buy healthier street foods (91.5%) if they were accessible. In the Prayagraj/Allahabad District, there is a sizable market for consumers of street food. Although street food is the majority of what is eaten, if healthier options are offered, people would be eager to buy them.